Developing and validating a knowledge, attitude, and practice questionnaire regarding dengue among secondary schoolchildren in Malaysia - Rahmat Dapari; Kalaivani Muniandy; Lim Chee Hwa; Suhaili Abu Bakar; Mohd Nasir Mohd Desa; Sukhvinder Singh Sandhu; Nooreen Farzana Mustapha; Mohd ‘Ammar Ihsan Ahmad Zamzuri; Mohd Rohaizat Hassan; Nazri Che Dom; Syed Sharizman Syed Abdul Rahim (Discover Social Science and Health)
Abstract Introduction Dengue is a viral disease borne by mosquitoes that infects humans that is a significant public health concern and socio-economic burden globally, especially in countries in the tropics and subtropics. Health education and community participation are the most powerful prevention strategies. Assessing local community knowledge, attitude, and practice (KAP) on dengue is essential for targeted interventions, as enhancing KAP helps communities recognize risks, adopt preventive attitudes, and implement effective measures to reduce dengue transmission. This study developed and validated a questionnaire on dengue KAP among secondary schoolchildren. Questionnaires serve as essential tools in research, allowing for standardized measurement of knowledge, attitudes, and practices, which supports accurate data collection and meaningful analysis. Methods The development and evaluation process (structure and content) involved consultations with eight experts including public health medicine specialists, medical officers, behavioural insights officer, academician, and entomologist, to ensure the relevance and comprehensiveness of the questionnaires. A QDengue-KAP questionnaire was administered to 30 secondary schoolchildren in Kuala Lumpur, Malaysia. The online questionnaire was self-administered, closed-ended, distributed anonymously, and participation was voluntary. Results The final questionnaire comprised four sections and 50 items after the initial version had undergone a rigorous evaluation to ensure its reliability and validity. The content validity index (CVI) and content validity ratio (CVR) values exceeded the minimum requirement and indicated that all items met the minimum standards for content validity. Compared to the initial version, the final version of the questionnaire had improved Cronbach alpha values for each dengue KAP domain: knowledge [Cronbach’s alpha: 0.765 (items: 15)], attitude [0.894 (15)], practice Part A [0.735 (15)], and practice Part B [0.876 (5)]. Thus, each statement in the Knowledge (K), Attitude (A), and Practice (P) domains was deemed valid through validity and reliability evaluation, ensuring their relevance and accuracy in assessing dengue-related factors. Conclusion The validation process demonstrated that each statement in the KAP domains was relevant, accurate, and aligned with the study's objectives, supported by expert validation and representation of the target population. This rigorous approach strengthens the validity and reliability of the questionnaire, making it a valid tool for assessing and improving dengue-related behaviours within the target population.